Use of a sternocleidomastoid rotational and cervical-fascial advancement flap for closure of a persistent mastoid cutaneous fistula. Issue 10 (10th October 2020) - Tsitsiou, Y; Mantelakis, A; Joshi, A
Abstract: Background: Post-auricular mastoid fistula is a rare occurrence. It typically appears following repeated soft tissue injury, and is commonly caused by chronic suppurative otitis media and repeated surgical treatments. Management is challenging, with few reported successful surgical techniques, which often have limited applicability. Case report: This paper presents the case of a 58-year-old male with a persistent right-sided post-auricular cutaneous mastoid fistula resulting from two previous mastoidectomies. Although the patient underwent two simple primary closures, the fistula recurred. This was successfully treated with a new technique utilising a sternocleidomastoid rotational and cervical-fascial advancement flap, which was completely healed at the one-year follow up without a recurrence of the fistula. Conclusion: This novel technique provided definitive obliteration of a persistent cutaneous mastoid fistula. Utilising a double-layered flap and a facelift incision results in excellent functional and cosmetic outcomes.